ANALISIS DAMPAK PENGGUNAAN GADGET TERHADAP PERILAKU SOSIAL ANAK - Susi Damayanti; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of technology has led to an increase in the number of gadget use among children. The use of gadgets has both positive and negative impacts. This study aims to analyze the impact of gadget use on children's social behavior. The research method used is a Literature Study by reviewing 12 national journals indexed by SINTA and 2 relevant reference books. The results of the study show that the wise use of gadgets can have a positive impact, such as increasing knowledge, creativity, and digital communication skills. On the other hand, excessive use of gadgets will have a negative impact on children's social behavior, such as reduced direct interaction, low empathy, and a tendency to be alone. Therefore, the role of parents and teachers is crucial in supervising, limiting screen time, and providing appropriate guidance to maximize the benefits and minimize the negative impacts of gadget use on children’s social development.